The Influence of the #MakeFetchHappen Campaign on MadForMakeup Brand Positioning - Dinanti, Aurelia Dara; Astuti, Sri Wahyuning (Program Studi Ilmu Komunikasi FBIK Unissula, 2024)
The cosmetics industry is currently a very competitive industry, with various brands competing to win the hearts of consumers. In this competition, brand positioning is the main key in differentiating oneself from competitors. A persuasive marketing campaign is also an important factor in influencing consumer perceptions of a brand. This research aims to investigate the influence of the #MakeFetchHappen campaign on MadForMakeup brand positioning. A total of 153 respondents who were Instagram followers and consumers of MadForMakeup participated in this research. This research applies a quantitative research approach with descriptive verification analysis through the use of Hypothesis Testing (T Test and F Test). The analysis results show that attitude got the highest percentage, namely 82.01%, indicating a positive response from respondents to the campaign. The main finding of this research is that the #MakeFetchHappen campaign has a significant influence on MadForMakeup’s brand positioning, with a percentage of 67.6%. The remainder, around 32.4%, is caused by other factors, so H1 can be accepted. This research provides valuable insights for cosmetic marketing practitioners in planning effective campaign strategies to strengthen their brand positioning in a competitive market.